PENINGKATAN PRODUKTIVITAS KELOMPOK IBU-IBU PKK DESA BONTO MATINGGI MELALUI MEDIA DIGITAL - Irmah Halimah; Supiati Supiati; Syamsinar Syamsinar (Jurnal Abdi Insani, 2023)
Bonto Matinggi Village is one of the developing villages in Tompobulu District, Maros Regency. One of the government's efforts to improve the welfare of village communities is to empower women to be more productive. The use of social media is one of the alternatives provided by the service team in order to increase productivity, especially for women in villages, the majority of whom are housewives. The aim of this activity is to increase the productivity of the PKK women's group in Bonto Matinggi Village through the use of digital media. This activity is expected to improve the welfare of women in the village. This service activity is carried out by providing training to participants on how to use digital media to earn additional income. Participants are trained to use one of the applications on their cellphones to market business products. From the results of the service, the result was that the implementation of the training in Bonto Matinggi Village was a new experience for women in the village, the majority of whom were members of the PKK Women's Group. The community service activities carried out increase the motivation of the participants to start doing business even if only at home. There are efforts to develop the potential and abilities they have so that in the future they will be able to increase family welfare or income in the village. There needs to be continuity of this activity in the form of assistance to participants so that the results of the training can be maximized. The conclusion of this service activity is that there is an increase in understanding for PKK mothers in Bonto Matinggi village in the use of digital media